Determination of Cattle and Buffalo Skin Crackers Using Polymerase Chain Reaction Restriction Fragment Length Polymorphism - Rulli Riana Dewi; Yuny Erwanto; Nanung Agus Fitriyanto (Jurnal Sain Veteriner, 2017)
The aim of this study was to determine of cattle and buffalo species based on cytochrome b gene using PCR-RFLP. Cattle and buffalo hides were obtained from a slaughterhouse in Yogyakarta and Kudus Regency. To confirm the effectiveness and specificity of this fragment, there are seven of DNA mixture samples in various levels. Isolate DNA samples were amplified using universal primer of cytochrome b gene, then PCR amplicon was digested by RsaI restriction enzyme.. The result showed that mitochondrial cytochrome b gene successfully amplified fragments of 359 bp. RsaI restriction enzyme was able to cleave buffalo cytochrome b gene into two fragment  (326 and 23 bp), while the cytochrome b gene of the skin cattle DNA was uncleaved. . In conclusion, this study indicated that mixture DNA of cattle and buffalo hides could be digested by RsaI restriction enzyme  and determination of the buffalo hides in mixture samples could be detected into  10% level. Furthermore, RsaI enzyme could be used to specific identification buffalo species. PCR-RFLP technology has a potential and reliable method to identify  of the existence of r buffalo hides in the mixture with other hides.